Vpliv klime na debelinsko rast macesna (Larix decidua Mill.) na zgornji gozdni meji v JV Alpah - Levanič, Tom (Zbornik gozdarstva in lesarstva, 2005)
The relationship between larch (Larix decidua Mill.) tree-ring widthsand climate was studied on 7 selected locations in the southeastern partof the Alps (Slovenian Alps). Analysis was performed for the 1900-2003 period, when 13 positive common and 17 negative common pointer years were identified. The response function analysis showed significant positive response (wide tree ring) of larch to above-average temperature in June and significant negative response to above-average temperature in March. Temporal stability of climate-growth relationship was tested using the Forward Evolutionary Interval Method (part of Bootstrapped response function procedurein DendroCLIM 2002). Results showed changes in response to climate asthe time approached 2003. Influence of the above-average temperature in Junewas becoming less important, while the above-average temperature in May appeared to gain importance. Besides, negative influence of the aboveaverage temperature in March was progressively gaining in its importance. Change of response is directly connected to the increasing winter temperatures at high altitudes in the last 10-15 years.
Keywords: Alpe; Alps; dendrokronologija; Larix decidua Mill.; macesen